Tracking attendance for reserve army via image processing / Muhammad Adnin Shahri - Shahri, Muhammad Adnin (2015)
An attendance tracking system is the easiest way to keep track the attendance of staffs within a company or an organization. Currently, attendance tracking systems are using biometrics, barcode, Bluetooth and manual methods. However in Bukit Beruang Askar Wataniah camp, they are still using manually in taking attendance which is inefficient. The reserve army needs to write their names, the time arrives and then sign the in a log book. This process is time consuming and it take time to enter their particular and other reserve army has to wait for their turn. Besides, the reserve army has another commitment because some of them work in other places and outside the camp area. Thus, it causes them to wrongly write the time in the log book. Therefore, in order to overcome these problems, image recognition project is conducted. It captures the serial number from the reserve army from identification card. In this project, the image processing is focusing on binarization technique to convert grayscale image to black and white image for further processing. The binarization is preserving edges and high-frequency parts of an image. The result from this project is 83.33% accuracy and the user will be able to reduce the reserve army time while taking attendance. It will also improve the efficiency of taking attendance with less error. In future, it can be enhance by generating the report based on the reserve army attendance information stored in excel.